The logic of concept expansion - Buzaglo, Meir, 1959- (Cambridge University Press, 2002)
"Scientists and mathematicians frequently describe the development of their field as a process that includes expansion of concepts. Logicians traditionally deny the possibility of conceptual expansion and the coherence of this description. Meir Buzaglo's innovative study proposes a way of expanding logic to include the stretching of concepts, while modifying the principles which apparently block this possibility. He offers stimulating discussions of the idea of conceptual expansion as a normative process, and of the relation of the conceptual expansion to truth, meaning, reference, ontology, and paradox, and analyzes the views of Kant, Wittgenstein, Godel, and others, paying especially close attention to Frege. His book will be of interest to a wide range of readers, from philosophers (of logic, mathematics, language, and science) to logicians, mathematicians, linguists, and cognitive scientists."--Jacket